A STUDY ON THE RELATIONSHIP BETWEEN GROUP COHESION AND ACHIEVEMENT MOTIVATION IN TEAM ATHLETES - Ercan Polat; Berna Can; Okan Şahin (ümit doğan üstün, 2019)
This study aimed to investigate the relationship between group cohesion and achievement motivation in team athletes according to various variables. In this research, the relational survey model, which is one of the general survey models, was used. The study group consisted of 359 high school and university students (138 females, 221 males) interested in team sports and studying at a level in Niğde. The study group was selected through an accidental sampling method, which is one of the convenience sampling methods. The questionnaire method was used as the data collection method. The questionnaire consisted of three parts. In the first part, we used a personal information form to obtain the demographic characteristics of the participants. In the second part, we used the three-dimensional Sports-Specific Achievement Motivation Scale (SSAMS) developed by Wills (1982) and adapted to Turkish by Tiryaki and Gödelek (1997). And, in the last part, we used the four-dimensional Group Cohesion Scale (GCS) developed by Carron et al. (1985) and adapted by Öcel and Aydın (2006). The questionnaire forms to be used in the research were delivered to the participants via face to face interview method. The data obtained from the research were analyzed using the SPSS program on the computer. When the findings were evaluated, a significant difference was found in the variables achievement motivation and group cohesion according to gender, educational background, team, and branch. Besides, there was a low negative and positive relationship between the variables age, sports year, monthly income, motivation for success, and group cohesion.